"De varejo eles entendem" : grupos familiares e redes de supermercados - Leandro, Hélio Wilson Santos (2014)
The second half of the twentieth century was a period of structural change in Brazil, beginning with the process of industrialization, which resulted in social and economic transformations, such as urbanization and modernization of the main cities of the country, the migration of rural population to cities, the emergence of new sectors in the economy, increasing jobs and income, etc.. But what draws the most attention is the reconfiguration of the profile of agents in economic spheres, from the 60s, which were sourced from family groups that increase in income, abruptly, and subsequently gained social recognition and acted only the sphere (economic), unlike the previous economic group, which conciliated activities in political and economic spheres. Thus, we aim to analyze, how was the formation of this second set of entrepreneurs in reality distinct, organized around family businesses, which are designed economically in the context in which the goods and services sector experienced the initiation and expansion "supermercadismo" in Brazil, from the 50s Therefore, we examine the political-economic context and illustrate the rise of entrepreneurial families through the formation of three supermarket chains: Paes Mendonça S / a, Bompreço (both family Paes Mendonça) and GBarbosa. The survey pointed out that the emergence of family groups in economic rise was a result of its investments in the grocery business, which received incentives from the federal government, creating a structure that favored their growth, however, went beyond, to show the weight of the model family business, since the key features needed in this economic sphere were incorporated into the family capital, thanks to the investments of the household members.